Telesna vadba pri bolnikih s kroničnim srčnim popuščanjem - Jug, Borut (Medicinski razgledi, 2000)
Exercise intolerance, a key symptom of chronic heart failure; has been linked to peripheral derangements, and marked endothelial dysfunction (i. e. the inability of endothelium to mediate a proper vasodilatatory response to physiologic stimuli) has been postulated to be one of the main causes. We hypothesized that supervised aerobic leg training improves endothelial function in the upper limb vessels. In our prospective study, 24 patients (3 women, 21 men, aged 50-80 years) with chronic heart failure were randomized toa control or a training group; which attended one-hour training sessions 3 times a week for 8 weeks. Before and after the training period, clinical and biochemical parameters, exercise capacity as well as endothelial dysfunction were determined. Endothelial dysfunction was assessed by high-resolution ultrasound measurements of brachial artery diameter and peak flow velocity at rest, after reactive hyperemia (causing flow mediated endothelium-dependent dilation), and after gylceriltrinitrate administration (causing endothelium-independent vasodilatation). (Abstract truncated at 2000 characters)
Keywords: Heart failure, congestive; srčno popuščanje; telesna vadba; Exercise test; Exercise therapy; Brachial artery; Ultrasonography